The Upshot Of Covid -19 On Sensex & Sectoral Indices In Indian Stock Market – A Comparative Analysis During Pre Covid & Covid Period - Nitha.K.P, Dr. S. Sivakumari, Dr.Suraj.E.S (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This paper focused on studying the impact of Covid-19 on stock market Index (BSE SENSEX), more specifically on sectoral Indices in Indian stock market. At the time of this research, there were millions of Covid cases taken place all over the world. The main aim of this system is to know the impact of Covid cases on sectoral performance specifically assist the investor for picking the stocks from each sector during the covid period. There are several other economic factors influence on the investment decisions and performance of the stock market indices in India during the covid period. In this research, contributing factors such as FII, Crude oil price, influence on stock market indices have been studied during the covid period. So this study found that Crude oil price is an important factor determining some sectoral Indices in Indian stock market during the covid period. This study also focused on performance of sensex and sectoral Indices during pre covid and covid period.